Técnicas Grafoplásticas para el desarrollo de la preescritura en niños de 3 años - Ubilla Carriel, Widinson Ivan (2025)
The objective of this study was to determine the contribution of graphoplastic techniques to the development of prewriting in 3-year-old children of the Juan E. Verdesoto Basic Education School during the 2024-2025 school year. The development of prewriting from an early age is essential to acquire fine motor skills that allow children to make strokes and recognize shapes, skills necessary for writing; however, in sublevel I of this institution, difficulties such as lack of control in the use of the pencil, poor recognition of basic shapes, and poor spatial orientation were identified. The research was developed under a qualitative approach and a non-experimental design, using the analytical-synthetic method to analyze the characteristics and effects of graphoplastic techniques, while data collection will be carried out through interviews with teachers and direct observation of the children. The instruments included questionnaires and observation sheets. The study population consisted of two teachers and 50 children, of which 25 made up the sample. As a result, areas were identified in which children have difficulties in their pre-writing development. It is concluded that graphoplastic techniques are pedagogical strategies that favor the development of pre-writing since they strengthen fine motor skills and coordination, with activities such as modeling, tearing and finger painting being activities that allow the improvement of control and precision in children's movements, being the bases for fluency in writing.